2020
DOI: 10.3892/etm.2020.8580
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib, a selective COX‑2 inhibitor, markedly reduced the severity of tamoxifen‑induced adenomyosis in a murine model

Abstract: The aim of the present study was to evaluate the effects of the selective cyclooxygenase (COX)-2 inhibitor celecoxib on the development of uterine adenomyosis in mice. ICR neonatal mice were first exposed to tamoxifen to establish a mouse model of adenomyosis. Following 60 days of celecoxib treatment, pathological formation of adenomyosis lesions and the depth of myometrial infiltration were evaluated using hematoxylin and eosin staining. To examine thermal pain modulation in mice, a hotplate test was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Regarding vascular density, it has been demonstrated that microvessels develop around adenomyosis lesions in the human adenomyosis 31,32 . In the present study, the vascular density progressively and significantly increased over time, which is consistent with findings made in studies using other mouse models of adenomyosis 17,18 . It is possible that the proliferation of these microvessels was responsible for the increase in the volume of adenomyosis lesions over time in our model.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding vascular density, it has been demonstrated that microvessels develop around adenomyosis lesions in the human adenomyosis 31,32 . In the present study, the vascular density progressively and significantly increased over time, which is consistent with findings made in studies using other mouse models of adenomyosis 17,18 . It is possible that the proliferation of these microvessels was responsible for the increase in the volume of adenomyosis lesions over time in our model.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the current study is the first one in which mice were allowed to deliver to analyze the status of adenomyosis after delivery. One advantage of our model over the previous model is that it does not require hormonal modification or oophorectomy, which can cause ovarian dysfunction or uterine thinning [13][14][15][16][17][18][19] and may affect the course of pregnancy. This study showed that the number and size of adenomyosis lesions did not change between the pre-pregnancy and post-partum period; therefore, this model may be helpful in modeling perinatal outcomes in pregnancies complicated by adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, 53% of patients in the tamoxifen-treated group were diagnosed with adenomyosis whereas only 18.2% of non-tamoxifen treated patients received a histologically confirmed diagnosis (Cohen et al, 1997). In addition to human data, animal studies have also revealed an association between tamoxifen exposure and the subsequent development of adenomyosis (Parrott et al, 2001;Green et al, 2005;Mehasseb et al, 2009;Jin et al, 2020).…”
Section: Tamoxifenmentioning
confidence: 99%